Twelve-Day Reinforcement-Based Memory Retention in African Cichlids (Labidochromis caeruleus) - Ingraham, Erica; Anderson, Nicole D.; Hurd, Peter L.; Hamilton, Trevor J. (Frontiers in Behavioral Neuroscience, 2016)
The formation of long-term memories for food sources is essential for the survival of most animals. Long-term memory formation in mammalian species has been demonstrated through a variety of conditioning tasks, however, the nature of long-term memory in fish is less known. In the current study, we explored whether African cichlids (Labidochromis caeruleus) could form memories for food-reinforced stimuli that last for 12 days. During the training sessions, fish were reinforced for approaching an upward drifting line grating. After a rest period of 12 days, fish demonstrated a significant preference for the upward drifting grating. To determine whether this preference could also be reversed, fish were then reinforced for approaching a downward drifting line grating after a 20-day rest period. When tested 12 days later, there were no significant differences in preference for either stimulus; however, following a second training period for the downward stimulus, there was a significant preference for the downward drifting grating. This suggests that cichlids are able to form reversible discrimination-based memories for food-reinforced stimuli that remain consolidated for at least 12 days.